2011
DOI: 10.1158/1940-6207.capr-11-0276
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intake and Colorectal Cancer Risk by Molecularly Defined Subtypes in a Prospective Study of Older Women

Abstract: Increased alcohol consumption is a putative colorectal cancer (CRC) risk factor. However, existing data are less conclusive for women than men. Also, to date, relatively few studies have reported alcohol-related CRC risks based on molecularly-defined tumor subtypes. We evaluated associations between alcohol intake and incident CRC, overall and by microsatellite instability (MSI-H or MSI-L/MSS), CpG island methylator phenotype (CIMP-positive or CIMP-negative) and BRAF mutation (mutated or wild-type) status in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…The present review found that the detrimental effect of high alcohol intake on the incidence of CRC was consistent with previous reports (Kontou et al, 2012;Park et al, 2009Park et al, , 2010; however, the results also suggested there was no increased risk for CRC when consuming up to 30 g/d of alcohol (Bongaerts et al, 2008;Grosso et al, 2014;Kontou et al, 2012;Nan et al, 2013;Park et al, 2010;Razzak et al, 2011;Zhao et al, 2012). The discrepancies between previous reports may be due to inappropriate stratification of alcohol intakes, with moderate intakes ranging from 12.6 to 49.9 g/d alcohol (Fedirko et al, 2011).…”
Section: No Associated Crc Risk For Moderate Alcohol Intakesupporting
confidence: 90%
See 4 more Smart Citations
“…The present review found that the detrimental effect of high alcohol intake on the incidence of CRC was consistent with previous reports (Kontou et al, 2012;Park et al, 2009Park et al, , 2010; however, the results also suggested there was no increased risk for CRC when consuming up to 30 g/d of alcohol (Bongaerts et al, 2008;Grosso et al, 2014;Kontou et al, 2012;Nan et al, 2013;Park et al, 2010;Razzak et al, 2011;Zhao et al, 2012). The discrepancies between previous reports may be due to inappropriate stratification of alcohol intakes, with moderate intakes ranging from 12.6 to 49.9 g/d alcohol (Fedirko et al, 2011).…”
Section: No Associated Crc Risk For Moderate Alcohol Intakesupporting
confidence: 90%
“…The reduced CRC risk associated with <30 g/d alcohol was found to be significant in only 2 studies: for nonobese individuals consuming between 13.5 and 27 g/d alcohol (Zhao et al, 2012), and for a Mediterranean population, where wine was a significant contributor to the alcoholic beverage type (Kontou et al, 2012). For all other studies, the risks associated with moderate alcohol consumption were not found to be statistically significant, but they consistently showed a reduced risk trend at moderate intake (Crockett et al, 2011;Nan et al, 2013;Park et al, 2010;Razzak et al, 2011).…”
Section: No Associated Crc Risk For Moderate Alcohol Intakementioning
confidence: 95%
See 3 more Smart Citations